2011
DOI: 10.5301/je.2011.8525
|View full text |Cite
|
Sign up to set email alerts
|

Female Perspectives on Endometriosis: Findings from the Uterine Bleeding and Pain Women'S Research Study

Abstract: Purpose The symptoms of endometriosis are heterogeneous and overlap with those of other conditions, resulting in misdiagnoses and/or delayed diagnosis and treatment. The Uterine Bleeding and Pain Women's Research Study (UBP-WRS) collected data to elucidate differences in diagnoses and treatment experiences of women, and to assess the impact of endometriosis on their quality of life. Methods The UBP-WRS interviewed women aged 15 to 49 in eight countries using an online methodology. Quotas were applied for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
71
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 25 publications
12
71
1
1
Order By: Relevance
“…Our survey captured a broadly representative patient sample, as opposed to specific sub-populations that might be receiving treatment for severe disease, experiencing specific endometriosis-related symptoms, or screened for surgery in a gynecology practice. Our results agree with the DE prevalence estimate of 6.6% for the US population reported by Bernuit et al [15] , who used a similar survey methodology. However, it is possible that 6.1% is an overestimation of overall DE prevalence because our study included women with a surgical diagnosis as well as women with presumptive endometriosis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our survey captured a broadly representative patient sample, as opposed to specific sub-populations that might be receiving treatment for severe disease, experiencing specific endometriosis-related symptoms, or screened for surgery in a gynecology practice. Our results agree with the DE prevalence estimate of 6.6% for the US population reported by Bernuit et al [15] , who used a similar survey methodology. However, it is possible that 6.1% is an overestimation of overall DE prevalence because our study included women with a surgical diagnosis as well as women with presumptive endometriosis.…”
Section: Discussionsupporting
confidence: 83%
“…Recent data from the United States suggest that the prevalence of endometriosis ranges from 6.6 to 16.2% [15] . However, consensus estimates in the United States have not been definitively established.…”
Section: Introductionmentioning
confidence: 99%
“…Pain is consistently reported as a central and destructive feature of life with endometriosis and several studies report a negative correlation between pain and QoL Sepulcri et al [24], Nnoaham et al [18], Souza et al [25], Tripoli et al [23]. Endometriosis symptoms, and specifically pain, have a detrimental impact on daily life and physical functioning (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There were 17 papers (14 quantitative and 3 qualitative) which reported findings relating to the impact of endometriosis on QoL [23], and one study demonstrated that a minority of women consider themselves to have a current state of health 'worse than death' Simoens S et al [7].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, endometriosis has a crucial impact on daily life and physical functioning (e.g. sleeping, eating and moving) [3,4,5], and the associated reduced energy and vitality [4] have a negative impact on social and sexual life [6,7,8,9]. There is no definitive treatment for endometriosis, either surgical or medical, and the main goal of management is to relieve symptoms by removing endometriotic lesions and/or limit the consequences of their growth [10].…”
Section: Introductionmentioning
confidence: 99%